Religion, State, and the Campus: Religious Moderation in the Context of Islamic Higher Education in Indonesia - Halid; Sulaiman, Setyadi; Mantu, Rahman; Sayogie, Frans; Al-Kaf, Idrus; Labib, Mughni (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2025)
This article examines campus-level understandings and attitudes toward religious moderation by drawing on data from students and academic representatives at three State Islamic Higher Education Institutions (Perguruan Tinggi Keagamaan Islam Negeri/PTKIN) in Indonesia: Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, UIN Sumatera Utara, and Institut Agama Islam Negeri (IAIN) Manado. These three PTKIN were selected because they represent different regions of Indonesia and therefore provide a comparative perspective on how campuses conceptualize and implement religious moderation. This study adopts a qualitative paradigm as its primary analytical framework while also employing survey techniques that require quantitative analysis of field data. Accordingly, the research utilizes a mixed-methods approach. The analytical perspective is grounded in state ideology and education policy frameworks, which are further supported by data obtained through interviews, focus group discussions (FGDs), and document analysis. The article also explores the potential, opportunities, and challenges involved in strengthening religious moderation among students. The findings indicate that the majority of new students participating in the Pengenalan Budaya Akademik dan Kemahasiswaan (PBAK) program remain within a moderate category and demonstrate significant potential to be guided toward understandings, attitudes, and behaviors that align with national policies on religious moderation. The expected contribution of this study is to provide empirical input and comparative data for policymakers, particularly within PTKIN, to support the development of more effective, systematic, and strategic approaches to the socialization and implementation of religious moderation in higher education. Abstrak: Artikel ini menjelaskan tentang pemahaman dan sikap kampus terhadap moderasi beragama dengan mengambil sampel para mahasiswa dan perwakilan akademik dari tiga Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) di Indonesia: Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, UIN Sumatera Utara, dan Institut Agama Islam Negeri (IAIN) Manado. Pemilihan tiga kampus PTIKN ini didasarkan pada alasan bahwa ketiganya menjadi representasi dari tiga wilayah Indonesia yang, secara umum, bisa mendeskripsikan keberadaan kampus dalam memahami moderasi beragama. nelitian ini menerapkan paradigma kualitatif sebagai referensi utamanya, tetapi juga menggunakan metode survei yang membutuhkan perhitungan kuantitatif dari data lapangan. Oleh karena itu, penelitian ini menggunakan metode penelitian campuran. Sedangkan pendekatan studi yang digunakan mengacu pada “kebijakan ideologi negara” dan “kebijakan politik pendidikan” yang diperkuat dengan wawancara, FGD (focus group discussion), dan dokumentasi. Kampus menjadi bagian penting dari kebijakan pemerintah dalam upaya membangun moderasi beragama di kalangan mahasiswa. Artikel ini juga menjelaskan adanya potensi, peluang, dan tantangan terkait penguatan moderasi beragama di kalangan mahasiswa. Hasil sementara menunjukkan bahwa sebagian besar mahasiswa baru yang mengikuti pelaksanaan PBAK tersebut, masih dalam kategori moderat dan berpotensi untuk terus dibina dan diarahkan pada pemahaman, sikap, dan perilaku yang sesuai dengan kebijakan pemerintah. Hasil yang diharapkan dari penelitian ini adalah diperolehnya beberapa masukan dan data banding bagi para pengambil kebijakan, khususnya di lingkungan PTKIN, agar sosialisasi moderasi beragama bisa diselenggarkan lebih baik, sistemik, dan strategis.